Stellar Evolution and Convection in 3D Hydrodynamic Simulations of a Complete Burning Phase - Federico Rizzuti; Raphael Hirschi; Vishnu Varma; William David Arnett; Cyril Georgy; Casey Meakin; Miroslav Mocák; Alexander StJ. Murphy; Thomas Rauscher (Galaxies)
Our understanding of stellar evolution and nucleosynthesis is limited by the uncertainties coming from the complex multi-dimensional processes in stellar interiors, such as convection and nuclear burning. Three-dimensional stellar models can improve this knowledge by studying multi-D processes, but only for a short time range (minutes or hours). Recent advances in computing resources have enabled 3D stellar models to reproduce longer time scales and include nuclear reactions, making the simulations more accurate and allowing to study explicit nucleosynthesis. Here, we present results from 3D stellar simulations of a convective neon-burning shell from a 20 M⊙ star, run with an explicit nuclear network from its early development to complete fuel exhaustion. We show that convection halts when fuel is exhausted, stopping its further growth after the entrainment of fresh material. These results, which highlight the differences and similarities between 1D and multi-D stellar models, have important implications for the evolution of convective regions in stars and their nucleosynthesis.